We should learn from lessons learnt - Abd Razak, Dzulkifli (2008)
SPOOFED! You're cooked and fried" read a recent headline (NST, Oct 5). Apparently, to spoof someone is as easy as buying an envelope, putting a stamp on it and writing a return name and address that's not your own, according to an information technology expert. We have been reminded yet again not to trust everything that we read digitally. What about the email on how to make a hardboiled egg using a mobile phone? A spoof? Maybe. How about the recent testimony by scientists warning the US Congress on cancer risks for cellphone users?